2020
DOI: 10.1186/s12987-020-00213-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic extradural compression of spinal cord leads to syringomyelia in rat model

Abstract: Background: Syringomyelia is a common spinal cord lesion. However, whether CSF blockage is linked to the formation and enlargement of syringomyelia is still controversial. The current model of syringomyelia needs modification to more closely mimic the clinical situation. Methods: We placed cotton strips under the T13 lamina of 40 8-week-old rats and blocked CSF flow by extradural compression. After 4 and 8 weeks, MRI was performed to evaluate the morphology of syringomyelia and the ratio of spinal cord diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…It is characterized by typical syrinx separation on imaging morphology, which we have initially confirmed in rat models of syringomyelia. 30 However, that still needs to be better understood whether it belongs to a transitional state of syringomyelia or a special configuration, which will certainly lead us to potential implications for the exploration of the hydrodynamics and biological mechanisms during syringomyelia formation and resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by typical syrinx separation on imaging morphology, which we have initially confirmed in rat models of syringomyelia. 30 However, that still needs to be better understood whether it belongs to a transitional state of syringomyelia or a special configuration, which will certainly lead us to potential implications for the exploration of the hydrodynamics and biological mechanisms during syringomyelia formation and resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Its particularity lies in that the reactivity following the change of CSF circulation seems to be more sensitive, and it shows stronger adaptability and reducibility than other types of syringomyelia, which not only reflects in the greater changes in the cervical lordosis during the syrinx formation with a shorter natural history but also in the more obvious syrinx resolution and a relatively better prognosis after removing the intradural obstruction and dredging the circulation of CSF. In terms of syrinx width, both moniliform type and distended type belong to the category with a larger S/C ratio; from the perspective of syrinx morphology, syrinx separation is the typical imaging manifestation for moniliform type, and some studies have preliminarily confirmed syrinx separation might be related with the ependymal cells surrounding the central canal of the spinal cord [ 29 , 30 ], which would be a source of endogenous stem cells, heralding a potential endogenous approach to SCI repair. While it is still unknown the specific pathophysiological mechanism of syrinx separation in chronic SCI.…”
Section: Discussionmentioning
confidence: 99%
“…S3), compromising the normal function of the corresponding spinal cord segments. Hence, to avoid potential bias arising from post-traumatic syringomyelia, data on metabolism at the T7-T8 vertebral level were discarded (36,37). Furthermore, data on metabolism at the T9-T11 level were not included in the statistical analysis because thoracic spinal cord segments mainly innervate the intercostal muscles for respiration, not locomotion (38).…”
Section: Pet-ct Quality Controlmentioning
confidence: 99%
“…Surgical management initially focused on treating the etiology of the syringomyelia, 9 primarily by re-establishing the physiologic pathways of cerebrospinal fluid (CSF) in the SAS. 10 Mostly, the surgical goal is to reconstruct the craniovertebral junction (CVJ) with duraplasty. 11 Previous studies have suggested that early diagnosis and surgical intervention such as posterior fossa decompression (PFD) have made it possible to reduce the size of the syrinx.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the widespread use of magnetic resonance imaging (MRI), there was an increasing number of patients screened with syringomyelia. Surgical management initially focused on treating the etiology of the syringomyelia [ 9 ], primarily by re-establishing the physiologic pathways of cerebrospinal fluid (CSF) in the SAS [ 10 ]. Mostly, the surgical goal is to reconstruct the craniovertebral junction (CVJ) with duraplasty [ 11 ].…”
Section: Introductionmentioning
confidence: 99%